IMPROVING THE PREVENTION AND TREATMENT OF COMPLICATIONS OF SPONTANEOUS BACTERIAL PERITONITIS IN PATIENTS WITH LIVER CIRRHOSIS OF VIRAL ETIOLOGY - Mukhammadieva Musharraf Ibrokhimovna (Galaxy International Interdisciplinary Research Journal, 2023)
Improving the prevention and treatment of complications of spontaneous bacterial peritonitis in patients with liver cirrhosis of viral etiology were studied. 118 patients with liver cirrhosis of viral etiology aged 18 to 69 years were examined. The distribution by sex in the groups showed that in the first group of 60 patients, 38 (63.3%) were male and 22 (36.7%) female, and in the second of 58 patients 27 (46.55%) and 31 (53.4%) respectively. The results of the conducted studies indicate that cytolytic changes in the liver, determined by the activity of serum transaminases and the cholestatic component of the disease, were more pronounced in patients with SBP.